Medalization of social legal consciousness in information age - Орденов, С. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article reveals the phenomenon of medialization in the Information age. The mass media are positioned as a key element of discursive reproduction and development of symbols and practices that form a certain sociocultural meaning of memorialized events in the postmodern period. Medialization is responsible for creation of an information picture of the world and the formation of images of reality. Jointing of pieces of information of various types and their conversion into senses, re-formatting of knowledge of one level for another, or else, creating in isolation from reality of semiotic formations and special knowlege constructs that have no meaning out of the media and socio-cultural context, are found in the process of medialization. This specific feature of medialization is used in countries with an unsteady legal system allowing symbolic manipulation with the legal awareness, turning it into an ecstatic state with the aim of more effective influence and management, which is connected with the hegemony of ruling groups, whose dominance directly correlates with the degree of people’s conviction in mainstream ideas.